PENGARUH PENAMBAHAN INDIGOFERA SP TERHADAP KUALITAS KIMIA FERMENTASI BATANG PISANG SEBAGAI PAKAN TERNAK - Nur Asma; Afrini Dona (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
A livestock business's ability to succeed is influenced by a number of variables, one of them being feed, which accounts for over 50% of production expenditures. Feeding is necessary for animals to achieve their fundamental requirements for survival, development, reproduction, and output. The purpose of this study is to investigate the effects of indigofera sp addition on the chemical quality of fermentation of banana stems. This study is an experiment with four repeats and five treatment levels. banana stem + 0% indigofera sp in treatment P0 control; banana stem + 10% indigofera sp in treatment P1; banana stem + 20% indigofera sp in treatment P2; banana stem + 30% indigofera sp in treatment P3; and banana stem + 40% indigofera sp in treatment P4. Dry matter (BK), organic matter (BO), crude protein (PK), and crude fiber (SK) are the characteristics that are measured. The findings indicated that there was no significant change (p>0.05) in the DM and BO concentrations caused by the addition of indigofera sp. Additionally, the addition markedly (p<0.01) reduced the crude fiber concentration and increased the crude protein level. This investigation discovered that the highest-quality banana stem fermentation was achieved when 40% indigofera sp was added.